THE EFFECT OF PDEODE'S STRATEGY IN THE ACQUISITION OF GEOGRAPHICAL CONCEPTS FOR STUDENTSOF THE FIFTH LITERARY GRADE OF GEOGRAPHY SUBJECT - Mahdi Hussein, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The study aims at knowing the effect of PDEODE in acquiring the geographical concepts in the students of the fifth literary branch for the Geography class, and in order to achieve the objective of the study the researcher has formulated the following hypothesis: there are no differences with statistical significance at level of significance (0.05) in acquiring the geographical concepts among an average of marks of the experimental group students studying geography by the use of PDEODE strategy and the students of the control group that studies the same subject in the same traditional method in testing the acquisition of the concepts and the sample of the study has included the students of the fifth literary branch in the Khournq preparatory school that belongs to the General Directorate of Education in AnnajafAlshraf for the academic year (2017-2018) and the(69) students are distributed on two groups that are the experimental and the control, whereas the experimental group would study in the mode of PDEODE strategy and the control group would study in the traditional method. The researcher has prepared the main plans about (20) for the two groups after he formulated the behavioral objectives that are (60), in addition to preparing the test of concept acquisition that consists of (60) testing items in the form of multiple choice and was confirmed for its validity, stability, difficulty, and discrimination coefficient, and then parity was made between the two groups in the variables of chronological age, previous academic achievement, and intelligence. The researcher has applied the experiment from the date of 22-Feb-2018 up to 22-April-2018; after that, the researcher has applied the test of concepts acquisition, and after correcting the answers, the researcher has reached the results that after being statistically analyzed with the use of the t-test, the results have shown that the students of the experimental group outperformed the students of the control group, and that is attributed to the use of the PDEODE strategy in teaching the geography subject and the acquisition of the geographical concepts. Where the researcher recommended the use of PDEODE strategy in teaching geography for the fifth literary grade and the need to pay attention to teaching geography because of its impact on the teaching and learning process. The researcher suggested conducting a similar study to the current one in other study subjects and conducting a similar study to identify the impact of the PDEODE strategy on other variables such as achievement and creative thinking.